ANALISIS KETENTUAN PEMENUHAN MODAL MINIMUM (CAPITAL ADEQUACY RATIO) SEBAGAI SALAH SATU INDIKATOR KESEHATAN BANK (Studi Kasus pada Bank Rakyat Indonesia yang Terdaftar di BEI Periode 2011—2015) - FITRIYANI FITRIYANI; DIDIN RASYIDIN WAHYU (Banque Syar'i : Jurnal llmiah Perbankan Syariah, 2018)
AbstractThe banking sector, particularly banks, as part of a financial has importantrole as an intermediary institution for the sectors involved in an economy,and therefore the health of banks needs to be given serious attention, because itinvolves people's lives for the parties concerned for owners, government, andpublic using bank services. This study discusses the analysis of the provisionsof minimum capital adequacy (CAR) as an indicator of the health of banks(case study at Bank Rakyat Indonesia listed on the Stock Exchange 2011—2015). The analysis showed that the study year 2011—2015 Bank RakyatIndonesia is considered a very healthy bank, in connection with theassessment matrix composites, categorized in one rank higher because theratio of CAR is very insignificant in comparison to the Capital AdequacyRatio set forth in the provisions, because a very high percentage of capitalgrowth compared with the percentage growth in RWA. Therefore, the bank'shealth assessment criteria CAR ratio > 11% in a very healthy predicate thatcan be seen from the year 2011 reached 14.96%, 2012 reached 17.43%, in2013 reached 18.13%, in 2014 reached 19.57 %, in 2015 reached 21.39%